Associative memory cells of encoding fear signals and anxiety are recruited by neuroligin-3-mediated synapse formation - Bingchen Chen; Yun Zhang; Huajuan Xiao; Lei Wang; Jiayi Li; Yang Xu; Jin-Hui Wang (Communications Biology)
Abstract Acute severe stress may induce fear memory and anxiety. Their mechanisms are expectedly revealed to explore therapeutic strategies. We have investigated the recruitment of associative memory cells that encode stress signals to cause fear memory and anxiety by multidisciplinary approaches. In addition to fear memory and anxiety, the social stress by the resident/intruder paradigm leads to synapse interconnections between somatosensory S1-Tr and auditory cortical neurons in intruder mice. These S1-Tr cortical neurons become to receive convergent synapse innervations newly from the auditory cortex and innately from the thalamus as well as encode the stress signals including battle sound and somatic pain, i.e., associative memory neurons. Neuroligin-3 mRNA knockdown in the S1-Tr cortex precludes the recruitment of associative memory neurons and the onset of fear memory and anxiety. The stress-induced recruitment of associative memory cells in sensory cortices for stress-relevant fear memory and anxiety is based on neuroligin-3-mediated new synapse formation.